STEM-SDGs Integration to Improve Scientific Communication Skills in Junior High School Science Learning - Rini, Norma Puspa; Putra, Pramudya Dwi Aristya; Ahmad, Nur (Jurnal Pendidikan MIPA, 2025)
Scientific communication is defined as verbal communication that is related to investigation. Science learning has an important part in the scientific communication skills that learners must have, which involves a scientific approach whose stages include observing, questioning, collecting data, evaluating data, and expressing conclusions. Scientific communication has an important role to be mastered by learners to succeed in science disciplines. This study aims to identify STEM-SDGs-based Students’ Worksheets used by students in supporting scientific communication skills on temperature, heat, and expansion material and analyze the scientific communication skills of junior high school students in discussing SDGs issues related to temperature, heat, and expansion. The method in this research uses a qualitative approach with a single case study research type. This research was conducted at MTSN 2 Jember in the odd semester of the 2024/2025 school year. The results showed that the application of STEM-SDGs-based Students’ Worksheets played a role in improving students' scientific communication skills. This is because the STEM-SDGs-based Students’ Worksheets has been prepared by 25% to support each indicator. The STEM approach that integrates various disciplines encourages students to actively participate and discuss, thus strengthening their understanding of complex scientific concepts. Based on the analysis of students' scientific communication skills after using the STEM-SDGs-based Students’ Worksheets, it was found that the highest student condition was in the fourth indicator, namely representation form (86%) with a very good category. While the lowest student condition in the third indicator, namely the use of scientific terms (code), which tends to be low with a deficient category (72%). The interview results show that students understand concepts related to SDGs and can explain scientific phenomena, but still use colloquial language rather than appropriate scientific terms.        Keywords: scientific communication, STEM, SDGs, temperature, heat, expansion.